Behaviors that Affect Online Shopping through Shopee Application of Consumers in Nakhon Pathom Province - Bumrungsuk, Pawana (Journal of Management Science Nakhon Pathom Rajabhat University, 2023)
There are two objectives of this research: 1) to study the behavior of online shopping through Shopee application of consumers in Nakhon Pathom Province when classified by behavior of using the internet to shopping online and 2) to study 6 marketing factors affecting decision to shop online via Shopee application of consumers in Nakhon Pathom Province. The researcher collected data from consumers in Nakhon Pathom area who had previously made purchases online products through an application, 400 people collect data using convenience selection method. The tool used was a questionnaire that has been validated for content validity and find an acceptable level of confidence. The statistics used in the data analysis consisted of percentage, mean, standard deviation, tests, one-way analysis of variance. and multiple regression analysis. The results showed that 1. Online shopping behavior through the Shopee application of consumers in Nakhon Pathom Province when classified according to the behavior of using the internet to shop online statistically significant 2. Marketing Factors Affecting Online Shopping Decisions via Shopee applications consumers in Nakhon Pathom Province consisted of products (b=0.141) price (b=0.102) distribution channels (b=0.180) marketing promotion (b=0.081) and privacy (b=0.321) The equation has a predictive power of 73.10 percent. The equation can be written as follows. Ŷ = 0.494 +0.141 x1 **+ 0.102 x2 *+ 0.180 x3 **+ 0.081 x4 *+ 0.067 x5 + 0.321 x6** Article history : Received 3 March 2021 Revised 20 May 2021 Accepted 28 May 2021 SIMILARITY INDEX = 2.19 %